A Semi-Instantaneous Heat Exchanger for Mobile Solar Collectors Test System - Haifeng Cao; Liangen Yang; Jiabao Cheng; Xing Cheng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A semi-instantaneous heat exchanger which can solve low efficiency and space shortage of mobil test system for thermal performance of solar collectors is proposed in this paper, In this paper, the structure parameters of heat exchanger and the power of heat resistance are designed based on the method of mean temperature difference. The experiment results show the performance of test system has been optimized. The efficiency of collectors test can be increased 50% and the total weight of the primary heater and working medium is reduced to 13.8%.The load of the test vehicle and occupancy volume have been decreased. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2860